Balancing Commercialization and Sustainability in Community-Based Tourism Practices - A Qualitative Study of Factors Affecting Elephant Habitat Communities in Northern Thailand - Lo, Yu-Chih; Janta, Pidpong (Frontiers in Psychology, 2021)
Community-Based Tourism (CBT) offers local residents opportunities to manage local tourism resources while sustain their lifestyle at the same time. The research objective of the study was to explore the process and experience of communities in Northern Thailand which are known as elephant habitats, how these communities strive for stimulating local economy without jeopardizing the way of life. The study was qualitative in nature. Qualitative data collection methods such as field observations, in-depth interviews were employed. The qualitative data were further analyzed with thematic analysis. In practicing CBT, the findings identified positive factors (Establishment of Elephant Camps), negative factors (Waste from Tourism Activity and Effects of Global Crisis on Employment and Local Income), and suggestions (Waste and Environment Management). The study found that the communities took pride in their cultural as well as natural resources and they are willing to commercialize these resources to a certain degree, i.e. founding elephant themed facilities has evidently indicated. Consequently, as many issues factoring in practicing CBT, the study concluded that community participation and government support should have played a crucial role in maintaining new balance of overall local lifestyle sustainability and commercialization during and after the pandemics.